Impacts of Green Synthesis Process on Asymmetric Hybrid PDMS Membrane for Efficient CO2/N2 Separation - Guo-Liang Zhuang; Chao-Fong Wu; Ming-Yen Wey; Hui-Hsin Tseng (Membranes, 2021)
The effects of green processes in hybrid polydimethylsiloxane (PDMS) membranes on CO2 separation have received little attention to date. The effective CO2 separation of the membranes is believed to be controlled by the reaction and curing process. In this study, hybrid PDMS membranes were fabricated on ceramic substrates using the water-in-emulsion method and evaluated for their gas transport properties. The effects of the tetraethylorthosilicate (TEOS) concentration and curing temperature on the morphology and CO2 separation performance were investigated. The viscosity measurement showed that, at specific reaction times, it is benefit beneficial to fabricate the symmetric hybrid PDMS membranes with a uniform and dense selective layer on the substrate. Moreover, the a high TEOS concentration can decrease the reaction time and obtain create the a fully crosslinked structure, allowing more efficient CO2/N2 separation. The separation performance was furtherly improved with in the membrane prepared at a high curing temperature of 120 °C. The developed membrane shows excellent CO2/N2 separation with a CO2 permeance of 27.7 ± 1.3 GPU and a CO2/N2 selectivity of 10.3 ± 0.3. Moreover, the membrane shows a stable gas separation performance of up to 5 bar of pressure.